El derecho de propiedad en la Constitución Española de 1978 - García Costa, Francisco M. (2023)
This paper analyzes the way in which the Spanish Constitution of 1978 regulates the right to private property, and, through this subject, some general conditions of the Spanish constitutional system. After examining the political and constitutional importance of the right to private property, the author studies article 33 of the Spanish Constitution, turning to the historical and ideological basis of the concept of property recognized in it, and also to the meaning of the social function principle.